Study of Predisposing, Enabling, Reinforcing Factors: Adolescent Participation in the Integrated Primary Care Program - Yulis Indriyani; Teguh Irawan; Afrida Isnania Khoiro; Imelia Febriliyanti; Andini Hidayah Fajriyah; Safira Imelda Sari; Muhammad Shodiqul ‘Amali; Muhammad Aulia Shidiq Nugroho; Anggita Dias Nurfandila (Ahmar Metastasis Health Journal, 2025)
Adolescent participation in the Integrated Primary Care (ILP) Program remains low in many rural areas in Indonesia, despite national efforts to strengthen primary health care as part of the Healthy Indonesia 2045 agenda. Limited studies have examined the determinants of adolescent engagement, as previous research has predominantly focused on ILP implementation among mothers, toddlers, and health cadres. This study aims to analyze the predisposing, enabling, and reinforcing factors influencing adolescents participation in ILP activities using Lawrence Green’s PRECEDE-PROCEED Model. A descriptive qualitative design was employed, involving 10 adolescents aged 10-24 years registered in the ILP Posyandu of Karanganyar Village, Tirto District, Pekalongan Regency. Additional triangulation informants included one village midwife, two ILP cadres, and two policy makers, all selected through purposive sampling. Data were collected through in-depth semi-structured interviews and analyzed thematically. The findings indicate that predisposing factors, particularly adolescents limited understanding of ILP objectives and benefits, contribute to low engagement, with some expressing fear of examination results. Enabling factors show that facilities, equipment, and financing are adequate, yet participation is hindered by scheduling conflicts with school hours, despite the close proximity of ILP locations to adolescents homes. Reinforcing factors emerged as the strongest influence, with active communication from health workers, moral encouragement from families, and strong peer support playing crucial roles in motivating adolescents to attend ILP activities. Overall, the study reveals that low participation is shaped by interacting barriers across cognitive, structural, and social domains. Strengthening adolescent health literacy, adjusting activity schedules, and enhancing family and peer-based reinforcement are essential to improving sustainable adolescent engagement in ILP services. These findings highlight the importance of community-centered strategies and cross-sector collaboration to support the on going transformation of primary health care at the village level.